Extraordinary structural complexity of ilmajokite: a multilevel hierarchical framework structure of natural origin. (2020) - Jr, Andrey A. Zolotarev; Krivovichev, Sergey V.; Ca´mara, Fernando; Bindi, Luca; Zhitova, Elena S.; Hawthorne, Frank; Sokolovaf, Elena
No abstract available